2007
DOI: 10.1002/jmv.20940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with antiretroviral resistance in HIV‐1‐infected children

Abstract: In the USA and West Europe, nearly 80% of HIV-1-infected adults, experiencing virologic failure, harbored virus strain resistant to at least one antiretroviral drug. Limited data are available on antiretroviral drug resistance in pediatric HIV infection. The aims of this study were to analyze prevalence of HIV-1 drug resistance and to identify risk factors associated with resistance in this population. Prevalence of genotypic resistance was estimated retrospectively in treated children who experienced virologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Although a participant might be adherent, their medications may not be taken as directed with respect to the timing of doses and timing of food consumption, which could reduce medication effectiveness (24). Children who have developed resistance would also not be expected to achieve viral suppression despite high levels of adherence; high prevalence of viral resistance has been identified in several cohorts of perinatally-infected children [3840]. Finally, children have greater difficulty in achieving optimal viral suppression than adults, which has been attributed to higher baseline viral load and differences in viral dynamics (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although a participant might be adherent, their medications may not be taken as directed with respect to the timing of doses and timing of food consumption, which could reduce medication effectiveness (24). Children who have developed resistance would also not be expected to achieve viral suppression despite high levels of adherence; high prevalence of viral resistance has been identified in several cohorts of perinatally-infected children [3840]. Finally, children have greater difficulty in achieving optimal viral suppression than adults, which has been attributed to higher baseline viral load and differences in viral dynamics (41).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In addition, children may have a more difficult time maintaining adherence to ARVs and thus maintaining adequate drug levels to prevent the development of virological failure and HIV drug resistance. 1,2,8 Determining the HIV genotypic or phenotypic resistance are frequently employed strategies to help guide the selection of ARVs for treatment naïve patients and for patients requiring adjustments in therapy as a result of inadequate virological response. 9 Both approaches have been shown to be beneficial in the care of HIV-infected adults, 9 but few studies have assessed their impact in the paediatric and adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, studies from both resource-rich and resource-limited settings suggest that antiretroviral-related resistance mutations develop in 44-94% of children failing PIbased ART, and many children develop multiclass drug resistance. [16][17][18][19][20] Antiretroviral resistance mutations that develop while on PI-based ART may lead to decreased susceptibility across many other PIs and limit future treatment options. 17,21 Historically, RTV-based regimens have been associated with suboptimal treatment responses, with only 36% of children achieving sustained virologic suppression in an early study.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Antiretroviral resistance mutations that develop while on PI-based ART may lead to decreased susceptibility across many other PIs and limit future treatment options. 17,21 Historically, RTV-based regimens have been associated with suboptimal treatment responses, with only 36% of children achieving sustained virologic suppression in an early study. 22 Pediatric AIDS Clinical Trials Group investigations have shown that response to ritonavir-based therapy in NTRIexperienced but PI-naive children was robust initially, with 55% achieving virologic suppression by 12 weeks, but only 32% maintained virologic suppression at 48 weeks.…”
mentioning
confidence: 99%